Respuesta :

Explanation:

The question states that factor completely

[tex]16x^2-25[/tex]

Concept:

To do this , we will use the principle of difference if tqo squares given below as

[tex]a^2-b^2=(a+b)(a-b)[/tex]

Take the terms to be represented in terms of a and b below as

[tex]\begin{gathered} 16x^2=a^2 \\ (4x)^2=a^2 \\ a=4x \\ \\ 25=b^2 \\ b^2=5^2 \\ b=5 \end{gathered}[/tex]

Hence,

By substituing the values, we will have

[tex]\begin{gathered} 16x^2-25=(4x)^2-5^2 \\ 16x^2-25=(4x-5)(4x+5) \end{gathered}[/tex]

Hence,

The final answer is

[tex]\begin{equation*} (4x-5)(4x+5) \end{equation*}[/tex]